Fungos micorrízicos arbusculares influenciam o desempenho hortícola de cultivares de morangueiro (Research, Society and Development, 2021)
The inoculation of strawberry cultivars with arbuscular mycorrhizal fungi (AMF) is a profitable and viable biotechnological tool, with potential to improve the horticultural performance of plants. However, this biotechnology is lacking and unknown to producers. The aim of the research was to investigate whether strawberry cultivars in the absence and presence of inoculation with AMF differ in their horticultural performance. The treatments, delineated in a bifactorial scheme, were four strawberry cultivars in the absence and presence of two AMF-based inoculants. The experiment was designed in randomized blocks, with three replications. The root system of ‘Albion’ cultivar showed the highest mycorrhizal colonization. Claroideoglomus etunicatum showed greater capacity to infect plant roots. ‘Portola’ was the most productive cultivar and ‘Albion’ and ‘Aromas’ produced strawberries with the highest levels of total anthocyanins. It is concluded that the use of mycorrhizal biotechnology enhances the levels of total flavonoids in fruits of the ‘Albion’ cultivar inoculated with the fungal species C. etunicatum. The root system of ‘Albion’ cultivar has greater mycorrhizal colonization. The fungal species C. etunicatum is more effective in colonizing the roots of the plant host. It is suggested to use the ‘Portola’ cultivar to obtain higher fruit yields and the ‘Albion’ and ‘Aromas’ cultivars for producers who aim to obtain strawberries with higher levels of total anthocyanins. ‘Aromas’ is recommended for those seeking a dual purpose (production and quality).